Victimology - Doerner, William G. (Routledge, 2017)
Definition and scope -- The scope of victimology -- Measuring criminal victimization -- Addressing the impact of victimization -- The costs of victimization -- Remedying the financial impact of victimization -- Remedying the non-financial impact of victimization -- Victim rights -- Types of victimization -- Traditional crimes -- Sexual battery -- Intimate partner violence -- Child maltreatment -- Crime and the elderly -- Hate crime victimization -- Victimization at school -- Victimization at work